Performance Analysis of Compressive Diffusion Normalized LMS Algorithm with Link Noises - Zhang, Sheng; Zheng, Wei Xing (IEEE International Symposium on Circuits and Systems proceedings, 2021)
In this paper, an investigation is launched into the compressive diffusion strategy in the presence of noisy communication links so as to develop the compressive diffusion double normalized least mean square (NLMS) algorithm. Based on the single update global weight-error model, an analytical formulation of the transient and steady-state results is made for the compressive diffusion double NLMS algorithm. These analytical results are instrumental to making a better understanding of the mean- square performance of the compressive diffusion strategy against link noises. Lastly, simulation study is carried out to validate the performance of the developed compressive diffusion double NLMS algorithm over adaptive networks subject to link noises.